Scalar quasinormal modes of anti-de Sitter static spacetime in Horava-Lifshitz gravity with U(1) symmetry - Lin, Kai; Qian, Wei-Liang [UNESP]; Pavan, A. B. (Amer Physical Soc, 2016)
In this paper, we investigate the scalar quasinormal modes of Horava-Lifshitz theory with U(1) symmetry in static anti-de Sitter spacetime. The static planar and spherical black hole solutions in lower energy limit are derived in nonprojectable Horava-Lifshitz gravity. The equation of motion of a scalar field is obtained, and is utilized to study the quasinormal modes of massless scalar particles. We find that the effect of Horava-Lifshitz correction is to increase the quasinormal period as well as to slow down the decay of the oscillation magnitude. Besides, the scalar field could be unstable when the correction becomes too large.